Intestinal microbiota profile in healthy Saudi children: The bacterial domain - El Mouzan, Mohammad; Al-Hussaini, Abdulrahman; Al Sarkhy, Ahmed; Assiri, Asaad; Alasmi, Mona (Saudi journal of gastroenterology, 2022)
Background: Knowledge of microbiota in health is essential for clinical research on the role of microbiota in disease. We aimed to characterize the intestinal microbiota in healthy Saudi children. Methods: In this community-based study, stool samples were collected from a randomly selected sample of 20 healthy school children of Saudi origin. The samples were frozen at -80°C till analysis. Bacterial DNA was isolated and libraries were prepared using the Illumina Nextera XT library preparation kit. Unassembled sequencing reads were directly analyzed and quantified for each organism's relative abundance. The abundance for each organism was calculated and expressed as the average relative percentage from phyla to species. Results: The median age was 11.3 (range 6.8-15.4) years, and 35% of them were males. The three most abundant phyla were Firmicutes, Bacteroidetes, and Actinobacteria accounting for 49%, 26%, and 24%, respectively. The most abundant genera included Bifidobacterium, Bacteroides, and Blautia accounting for 18.9%, 12.8%, and 8.2%, respectively. Finally, the most abundant species included 14 species belonging to the genus Bacteroides and nine species belonging to Bifidobacterium. Conclusions: The abundance of intestinal microbiome in healthy Saudi children is different from that of other populations. Further studies are needed to understand the causes of variation between populations, which might lead to new preventive methods and treatment strategies of diseases caused by microbial dysbiosis.